2016
DOI: 10.1021/acsami.6b03425
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Affinity 3D Macroporous Graphene/MWCNTs/Fe3O4 Foams for High-Performance Microbial Fuel Cells

Abstract: Promoting the performance of microbial fuel cells (MFCs) relies heavily on the structure design and composition tailoring of electrode materials. In this work, three-dimensional (3D) macroporous graphene foams incorporated with intercalated spacer of multiwalled carbon nanotubes (MWCNTs) and bacterial anchor of Fe3O4 nanospheres (named as G/MWCNTs/Fe3O4 foams) were first synthesized and used as anodes for Shewanella-inoculated microbial fuel cells (MFCs). Thanks to the macroporous structure of 3D graphene foam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 63 publications
0
43
0
1
Order By: Relevance
“…The continuous horizontal CVD monolayer graphene coating consistently had no deleterious effects on attachment or survival of either bacterial or mammalian cells. This highlights the possibility to use such surfaces for fabrication of bioelectrodes or biosensors, where conductivity properties of graphene can be exploited without harming the cells. By contrast, PECVD‐grown, vertically aligned graphene coating had a pronounced killing effect and effectively prevented attachment of bacteria to the coated surfaces while being harmless to mammalian cells.…”
mentioning
confidence: 99%
“…The continuous horizontal CVD monolayer graphene coating consistently had no deleterious effects on attachment or survival of either bacterial or mammalian cells. This highlights the possibility to use such surfaces for fabrication of bioelectrodes or biosensors, where conductivity properties of graphene can be exploited without harming the cells. By contrast, PECVD‐grown, vertically aligned graphene coating had a pronounced killing effect and effectively prevented attachment of bacteria to the coated surfaces while being harmless to mammalian cells.…”
mentioning
confidence: 99%
“…The maximum output power densities of MSMFCs are 296.11 mW·m −2 (blank), 619.38 mW·m −2 (DAQ), 517.82 mW·m −2 (MWCNTs), and 890.12 mW·m −2 (DAQ/MWCNTs composite), respectively (Figure ). Based on what we have done, the maximum output power density of composite modified MSMFC is higher than that of other methods . The output power and the corresponding current of MSMFC have been improved after the composite modification, which demonstrates a significant improvement in output power by using the mentioned method.…”
Section: Resultsmentioning
confidence: 68%
“…To improve the interaction between anode and microorganisms, MWCNTs are usually composited with polymers, electron‐transfer mediator, and so on. The latest researches show that MWCNTs can enhance the electron‐transfer rate, thereby improving the output power and stability of MFCs . But these modification may have disadvantages, such as complicated preparation process and low power.…”
Section: Introductionmentioning
confidence: 99%
“…As the anodes can affect the power output of MFC, it is necessary to synthesize functional materials and design new structures for MFC anodes. The extracellular electron transfer between bacteria and the newly designed anodes can be improved, providing an alternative way to increase the power output density of MFC …”
Section: Introductionmentioning
confidence: 99%
“…The extracellular electron transfer between bacteria and the newly designed anodes can be improved, providing an alternative way to increase the power output density of MFC. 4,5 Composed of 2D sp2 hybridized carbon atoms, graphene is now considered as a new material for anode, [6][7][8] which attributes to its high specific surface area and excellent electrical conductivity. It has been reported that graphene can strengthen electron transfer rate between anode and bacteria, which significantly improves the output power density of MFC.…”
Section: Introductionmentioning
confidence: 99%